Modeling and Analysis of a Dual-Band Dual-Polarization Radiator Using FEKO - Zaghloul, Amir I.; Kawser, M. T.; Ravipati, C. Babu (Applied Computational Electromagnetics Society Journal (ACES), 2022)
A dual-band hybrid antenna element comprising of microstrip and waveguide radiating elements is theoretically investigated through computer simulations. The low band radiator is a Shorted Annular Ring (SAR) microstrip antenna and the high band antenna is an open ended circular waveguide. First, the characteristics of a SAR patch antenna are presented and reviewed. Then the dual-band antenna configuration is described, which is realized by forming a waveguide radiator in the shorted region of the SAR microstrip antenna. Modeling and analysis of the SAR patch antenna and the hybrid element are investigated using the method-of-moment-based software package FEKO. The analysis includes return loss computations showing the element bandwidth at different frequency bands and the radiation patterns in the E- and H- planes. Feeding the element in phase quadrature produces circular polarizations (CP). The radiation patterns of the CP dual-band element are also analyzed using FEKO and the axial ratio performance is subsequently assessed